Proteinuria: Basic Mechanisms, Pathophysiology and Clinical Relevance - Blaine, Judith (Springer International Publishing : Imprint: Springer, 2016)
Recent work has begun to elucidate at the molecular level how albumin is handled by the kidney and how albuminuria develops in various proteinuric diseases including minimal change disease and focal segmental glomerulosclerosis. This volume provides a comprehensive overview of the renal handling of albumin - from basic mechanisms to the pathophysiology of proteinuric diseases. In describing the basic mechanisms of albuminuria, a particular highlight will be the focus on advanced imaging techniques such as intravital microscopy that have allowed a detailed "window" into albumin transit through the kidney. The volume will cover the epidemiological studies which show that albuminuria is a strong and independent marker of kidney disease progression and cardiovascular events, the molecular details of albumin handling in the kidney at the level of the glomerulus and the proximal tubule and the pathophysiology of proteinuric diseases including minimal change disease, membranous nephropathy, focal segmental glomerulosclerosis and diabetic nephropathy.